Effects of Different Pretreatment Methods and Dietary Factors on the Form and Bioavailability of Iodine in Laminaria japonica. Issue 2 (7th February 2022) - Sun, Nan; Sun, Bolun; Li, Chao; Zhang, Jinjie; Yang, Wenge
ABSTRACT: The present study was aimed to evaluate the effects of different pretreatment methods (soaking, boiling, steaming) and dietary factors (ascorbic acid, citric acid, oxalic acid, phytic acid, tyrosine) on the bioavailability of iodine from Laminaria japonica by using In vitro simulated gastrointestinal digestion combined with Caco-2 cell model. The results showed that steamed L. japonica had the highest retention of iodine content (83.30 ± 3.91%), while boiling led to the largest iodine loss (38.46 ± 1.96%). Moreover, boiled L. japonica exhibited the greatest bioavailability (47.12 ± 5.28%) followed by steamed L. japonica (43.60 ± 3.05%). The presence of ascorbic acid, citric acid, or tyrosine promoted the cellular iodine absorption, while oxalic acid and phytic acid produced inhibitory effects. These findings suggested that the pretreatment methods and dietary factors could influence the actual intake of L. japonica sourced proteins and iodine by regulating their digestion characteristics and bioavailability.